Experimental evidence for effective flexural-only stiffnesses to account for nonlinear flexural-slip behaviour of timber-concrete composite sections. (15th September 2017) - Sebastian, W.M.; Bell, O.G.A.; Martins, C.; Dias, A.M.P.G.
Highlights: Concept of equivalent section flexural stiffness, variable along TCC span. Unique instrumentation layout to generate data to validate this concept. Demonstration that gamma method can be significantly improved upon using this approach. Illustration that nonlinear behaviour can be dealt with without unduly complex computations. Abstract: The nonlinear behaviours of timber-concrete composite (TCC) members can be predicted via linear beam element analyses. The key is to quantify effective flexural-only stiffnesses ( B ) that capture the material nonlinearities from flexure-slip action of the TCC section, and to conduct the analyses using B profiles which satisfy equilibrium, compatibility and nonlinear constitutive links to the connections. This paper demonstrates the manner in which ad-hoc instrumentation of a TCC specimen can underpin validation of that concept. The test-based nonlinear B profiles along the span are found to out-perform the Gamma method (which assumes uniform B ) in load response prediction. Finally, future research to broaden this approach is outlined.